Development of guided discovery-based mathematics learning tools to enhance problem-solving skills in high school students - Putri, Wina Friliza; Musdi, Edwin (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: Many students struggle with solving mathematical problems, which prevents them from achieving learning goals. To address this issue, this study develops learning tools designed to improve these skills.Aim: The goal of this study is to create guided discovery-based mathematics learning tools that are valid, practical, and effective in enhancing students' problem-solving abilities.Method: This study uses the Plomp development model, which includes three main stages: the initial investigation, development, and evaluation phases. The focus of this research is on the development of modules and student worksheets (LKPD).Results: The validity of the products was assessed by experts in terms of content, language, and presentation, all of whom found the products to be valid and ready for use. The practicality of the tools was confirmed through feedback from both students and teachers, showing that they are very practical. The effectiveness of the tools in improving problem-solving skills was high, with an effectiveness score of 0.749.Discussion: The results indicate that the developed mathematics learning tools are valid, practical, and effective. Therefore, they can be used in the classroom without requiring significant changes.